1999
DOI: 10.1103/physrevb.60.9999
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical and thermodynamical instabilities in the disorderedRexW1xsystem

Abstract: The dynamical and thermodynamical stability of the bcc and fcc disordered Re x W 1Ϫx system is studied within the density-functional theory. The configurational part of the free energy is obtained from ab initio electron structure calculations together with the cluster expansion and the cluster variation formalism. Electronic excitations are accounted for through the temperature-dependent Fermi-Dirac distribution. The lattice dynamics of Re and W is studied using the density-functional linear-response theory. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 56 publications
4
25
0
Order By: Relevance
“…1 for the ten elastically stable fcc structures revealing that all structures (Sc, Ti, Co, Y, Zr, Tc, Ru, Hf, Re, and Os) are in fact dynamically stable. We note that dynamical stability of fcc Co and fcc Re at 0 K was reported in previous studies of their lattice dynamical properties [20,57].…”
Section: A Elements With Stable Hcp Structuresupporting
confidence: 74%
“…1 for the ten elastically stable fcc structures revealing that all structures (Sc, Ti, Co, Y, Zr, Tc, Ru, Hf, Re, and Os) are in fact dynamically stable. We note that dynamical stability of fcc Co and fcc Re at 0 K was reported in previous studies of their lattice dynamical properties [20,57].…”
Section: A Elements With Stable Hcp Structuresupporting
confidence: 74%
“…This model has been commonly used to interpret neutron scattering measurements of phonon dispersion curves in the case of disordered alloys Nagel et al, 1995). It has also been used in a some theoretical investigations (Cleri and Rosato, 1993;Persson et al, 1999). However, the virtual crystal approximation has been repeatedly shown to be insufficiently accurate for the purpose of calculating differences in vibrational entropies between distinct compounds (Althoff et al, 1997;Ravelo et al, 1998;Shaojun et al, 1998).…”
Section: Appendix C: Modeling the Disordered Statementioning
confidence: 99%
“…7,11,[15][16][17][18][19] Here, Grimvall et al 12 and Persson et al 20 have suggested that dynamical instability of the hcp Mo plays a decisive role.…”
Section: Introductionmentioning
confidence: 98%